MAKNA MOTIF TOMBAK KUNTUL NGLANGAK DALAM KARYA BATIK - Nanda Delva Fitriyah; Muh Fakhrihun Naam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the general public’s particularly students’ lack of knowledge regarding the “tombak kuntul nglangak” motif and the symbolic meanings embedded in its form and application as a batik motif. In fact, this motif holds significant philosophical and cultural value as part of the preservation of traditional heritage through the art of batik. The objective of this study is to uncover and explain the meaning of the tombak kuntul nglangak motif in batik works using Charles Sanders Peirce’s semiotic approach. The method employed is qualitative descriptive, with data collection techniques including observation, interviews, literature review, and documentation conducted at several locations in Jepara and Surakarta, involving heritage collectors, museum curators, and batik artisans. The results of the study indicate that the tombak kuntul nglangak motif carries profound symbolic meanings, serving as a representation of life values, spirituality, and cultural identity. This motif functions not only as an aesthetic element but also as a medium for cultural education and preservation, capable of enhancing public understanding of traditional heritage and enriching innovation in the art of batik.